EPIDEMIOLOGY OF AMERICAN TEGUMENTENT LEISHMANIASIS IN THE FEDERAL DISTRICT AND THE IMPORTANCE OF THE MULTIDISCIPLINARY APPROACH - Rodrigues Junior, Edis; Gomes Abreu, Abraao; Almeida Sarmento, Carolyne; Lima Luz, Liniker; Roiz Casarin, Thays; Cristina Barbosa Serejo, Letícia; Sandy Barbosa de Lima, Lindsay; Lannara Freire e Silva, Aianne; Boni Inácio, Lucas; Rangel de Freitas Rodrigues, Ricardo; Gomes de Jesus, Suely; Kryssia Bastos Teles, Thamyres; et al. (Health and Society, 2024)
Introduction: American Tegumentary Leishmaniasis is an infectious, non-contagious disease, with compulsory notification and severe evolution, caused by protozoa of the genus Leishmania. The medications used for treatment are multidisciplinary approach strategies. Objective: To survey the epidemiological profile of a decade, 2009 to 2019, specifically in the Federal District, with the participation of a multidisciplinary approach in treatment. Methods: The procedures involved stages of preparing maps and graphs using the Power Bi program, to identify numbers of confirmed cases, with data by administrative regions of the Federal District, with treatment analysis. The epidemiological survey was carried out using data from SINAN and the Epidemiological Information on Leishmaniasis of the Federal District. Results: It was evident that the treatment is carried out at the reference center, Hospital Universitário de Brasília. Epidemiological information by Health Superintendencies, with constant case records, however in 2019 there was a significant decrease. Conclusion: It is pointed out that confirmed cases during the decade fluctuated and were recurrent. Participation in treatment, within the scope of the multidisciplinary approach, is necessary and requires, in addition to dispensing, monitoring the use of the medication by the patient, it is important to guarantee safety and effectiveness, guaranteeing health quality, avoiding errors related to medication.